Conceito de liberdade no pensamento de Rosa Luxemburgo - Leonardi, Sabrina Bortollotte Penteado (Universidade Federal de São Carlos, 2019)
The present final paper investigates in the political-philosophical works of Rosa Luxembourg, which consists the conception of freedom for the working masses. In view of this, it deals with contents that directly touch or treat this subject-matter and that help in its elucidation. Thus, it deals with elements of the philosopher's analysis of the First World War, the Russian Revolution and the crisis of German social democracy and still addresses the alternative between socialism and barbarism. It comes to the consideration that the masses, when determining socialism as a method and purpose, begin to take over their history, are guided against the drift of events that subjugate them, give conscious meaning to their actions, and thus progressively acquire their emancipation. The conclusion of these it is a requirement that this process be the result of the action of the masses and not of some other agent.
The concept of freedom in the Rosa Luxemburg's thought
Keywords: liberdade; história; social-democracia; socialismo; barbárie; CIENCIAS HUMANAS::FILOSOFIA::HISTORIA DA FILOSOFIA